TYPE SELECTION AND JUSTIFICATION OF THE PARAMETERS OF GRANADELLA COMBINATION UNIT - Igamberdiev Anvarjon Uktamovich (Bright Mind Publishing, 2025)
In clause reduction results of researches on shall choose types and substantiation of parameters a crest educational of the combined unit for the minimal processing of ground.
Keywords: Combination unit, a spherical disk, granetelli, the height of the ridge, the transverse profile of the comb, the diameter of the disc, the traction resistance of the working body, the quality of crumbling soil.